Harmony and Rhyme in the Quran - Mammadov, Nasrulla (Scholarya Demo Journal of Ruby, 2019)
The article sets forth the questions of revelation of the Quran in a style different from the style of the Arabs in Jahiliyya period. It is noted that one of the features proving the authenticity of the divine text, testifying to its special metaphor, is its presentation, rhyme and harmony. One of the imporant features that Factors that urge people to follow special rules and a peculiar melody while reading this heavenly book, are the corresponding verses of the Quran and the hadith of the Prophet. The author mentions 6 specific features of the individual character of the Quranic style differing from saj in the Arabic prose and stanza in the Arabic poetry. He draws certain parallels and comparisons to answer the baseless statements of Western orientalists about the existing division of the Quranic ayahs and to prove that the word Allah is based on stable rules and that the ideas of these philosophers are not true. According to the author, the structure of the Qur’anic surahs and ayahs, its composition, expression and style, its meanings, harmony and tone distinguish it from all literary examples created by human thought, confirming that the word Allah is a unique literary example.